Plasma Amino Acid Profiling in Major Depressive Disorder Treated With Selective Serotonin Reuptake Inhibitors - Woo, Hye‐In (CNS Neurosci Ther, 2015)
AIMS: Amino acids are important body metabolites and seem to be helpful for understanding pathogenesis and predicting therapeutic response in major depressive disorder (MDD). We performed amino acid profiling to discover potential biomarkers in major depressive patients treated with selective serotonin reuptake inhibitors (SSRIs). METHODS: Amino acid profiling using aTRAQ (™) kits for Amino Acid Analysis in Physiological Fluids on a liquid chromatography–tandem mass spectrometry (LC‐MS/MS) system was performed on 158 specimens at baseline and at 6 weeks after the initiation of SSRI treatment for 68 patients with MDD and from 22 healthy controls. RESULTS: Baseline alpha‐aminobutyric acid (ABA) discriminated the patients according to the therapeutic response. Plasma glutamic acid concentration and glutamine/glutamic acid ratio were different between before and after SSRI treatment only in the response group. Comparing patients with MDD with healthy controls, alterations of ten amino acids, including alanine, beta‐alanine, beta‐aminoisobutyric acid, cystathionine, ethanolamine, glutamic acid, homocystine, methionine, O‐phospho‐L‐serine, and sarcosine, were observed in MDD. CONCLUSION: Metabolism of amino acids, including ABA and glutamic acid, has the potential to contribute to understandings of pathogenesis and predictions of therapeutic response in MDD.